Insights from Malaysian World Heritage Sites on Heritage Sustainability - KRISHNAPILLAI, Geetha; ISA, Filzah Md. (Journal of Environmental Management and Tourism, 2025)
This study explores the role of domestic tourists in heritage sustainability, focusing on Malaysia's World Heritage Sites (WHS) since most literature focuses on local communities and international tourists. Extending the Value-Attitude-Behavior (VAB) model with additional variables, this study examined domestic tourists' value on sustainability, attitude, norms, moral obligation, and participation behavior related to heritage sustainability. Subsequently, the moderator of the Big Five Personality traits was also applied in the research model. The results found that value on sustainability significantly influenced the attitude, norms, and moral obligation of domestic tourists where social and subjective norms, through a vital bottom-up approach, are not merely beneficial but essential for ensuring the longevity of these heritage sites for future generations. Furthermore, openness, extraversion, extraversion, and agreeableness partially moderate the relationship between attitude, norms, moral obligations and heritage sustainability participation behavior in the VAB model.   This study provides a novel contribution in heritage sustainability studies particularly addressing the sustainability of WHS and using the VAB model and employing the MGA in analyzing the moderator of the Big Five Personality traits. Subsequently, the Important-Performance Analysis was also performed which identified that both social and subjective norms can drive significant behavioral changes among domestic tourists. It is recommended that future research employ controlled variables such as age and gender to have a deeper understanding of consumer behavior. This paper presents a robust theoretical framework in behavioral research which serves as a solid foundation for further exploration in sustainability domains.